Teaching digital literature in Arab and non-Arab universities: obstacles and solutions Preparation - Dr. Abdul-Saboor,; Dr. Noha Ibrahim Al-Desouki Gameel, (Al-Qanṭara, 2024)
This research paper titled “Barriers to Teaching Digital Literature in Egyptian Universities” delves into the obstacles faced by higher education institutions in Egypt regarding the adoption and instruction of digital literature. Presented at the Third International Arabic Language Conference organized by the Association of Scholars for Islamic Studies in Indonesia in collaboration with several Islamic and Arab universities, this study explores the impact of the rapid technological advancements and the shift towards a knowledge society on educational policies, strategies , and methodologies. The paper identifies digital literature as an emergent field necessitated by the digital transformation in education, emphasizing the need for universities to transition from traditional teaching methods to innovative approaches that incorporate technology and interactive learning. It outlines the primary challenges and barriers, including administrative, financial, and technical issues, that hinder the effective teaching of digital literature in Arab and non-Arab universities. By addressing key questions such as the definition, emergence, and characteristics of digital literature, and the historical transition of Arab literature from oral traditions to digital forms, this study aims to shed light on the critical obstacles and proposes recommendations to overcome them. The research employs a descriptive methodology to analyze the phenomenon as it exists, providing both qualitative and quantitative insights to understand the present challenges and predict future trends. Ultimately, this research underscores the importance of digital transformation in education, particularly in the field of literature, and advocates for comprehensive strategies to integrate digital literature into university curricula to enhance educational outcomes and competitiveness in the knowledge era.